Effects of Environmental Conditions on the Fitness Penalty in Herbicide Resistant Brachypodium hybridum - Frenkel, Eyal; Matzrafi, Maor; Rubin, Baruch; Peleg, Zvi (Frontiers in Plant Science, 2017)
Herbicide-resistance mutations may impose a fitness penalty in herbicide-free environments. Moreover, the fitness penalty associated with herbicide resistance is not a stable parameter and can be influenced by ecological factors. Here, we used two Brachypodium hybridum accessions collected from the same planted forest, sensitive (S) and target-site resistance (TSR) to photosystem II (PSII) inhibitors, to study the effect of agro-ecological parameters on fitness penalty. Both accessions were collected in the same habitat, thus, we can assume that the genetic variance between them is relatively low. This allow us to focus on the effect of PSII TSR on plant fitness. S plants grains were significantly larger than those of the TSR plants and this was associated with a higher rate of germination. Under low radiation, the TSR plants showed a significant fitness penalty relative to S plants. S plants exhibiting dominance when both types of plants were grown together in a low-light environment. In contrast to previous documented studies, under high-light environment our TSR accession didn’t show any significant difference in fitness compared to the S accession. Nitrogen deficiency had significant effect on the R compared to the S accession and was demonstrated in significant yield reduction. TSR plants also expressed a high fitness penalty, relative to the S plants, when grown in competition with wheat plants. Two evolutionary scenarios can be suggested to explain the coexistence of both TSR and S plants in the same habitat. The application of PSII inhibitors may have created selective pressure toward TSR dominancy; termination of herbicide application gave an ecological advantage to S plants, creating changes in the composition of the seed bank. Alternatively, the high radiation intensities found in the Mediterranean-like climate may reduce the fitness penalty associated with target-site resistance. Our results may suggest that by integrating non-herbicidal approaches into weed-management programs, we can reduce the agricultural costs associated with herbicide resistance.